10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
INTRODUCTION: Circuit clotting during polymyxin B hemoperfusion (PMX-HP) therapy could be associated with poor clinical outcomes in patients with septic shock. METHODS: This post hoc sub-analysis of the BEAT-SHOCK registry included 82 of 309 adults with septic shock requiring high-dose norepinephrine (≥ 0.2 μg/kg/min) that underwent PMX-HP therapy. We compared 28-day mortality between patients with and without circuit clotting during the first session. RESULTS: Among 82 patients (median PMX-HP duration, 1016 min), 25 patients (30%) had premature termination due to circuit clotting of those patients, 28-day mortality was 16% (4/25), as compared with 18% (10/57) in those without circuit clotting (adjusted hazard ratio 0.58; 95% confidence interval 0.13-2.55). Lower serum albumin was associated with circuit clotting (adjusted hazard ratio 0.48; 95% confidence interval 0.27-0.85; per 1 g/dL increase). CONCLUSIONS: Circuit clotting occurred in one-third of patients but was not associated with poorer outcomes. TRIAL REGISTRATION: UMIN Clinical Trial Registry, registration no. UMIN000038302.